2009
DOI: 10.1111/j.1524-4725.2009.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Childhood Hemangiomas Treated with the Pulsed-Dye Laser with Dynamic Cooling

Abstract: Early treatment of childhood hemangiomas with the 595-nm LP-PDL with dynamic cooling may reduce the proliferative phase and result in excellent rates of clearing and few adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 16 publications
1
81
1
4
Order By: Relevance
“…151 The controversy over laser use was recently rekindled by a study that showed an advantage to early laser management. 282 Although small IHs may be treated without sedation, children with larger lesions often require general anesthesia. Recent data suggest that early exposure to general anesthesia may have a negative effect on learning and behavior.…”
Section: Laser Therapy For Ihmentioning
confidence: 99%
“…151 The controversy over laser use was recently rekindled by a study that showed an advantage to early laser management. 282 Although small IHs may be treated without sedation, children with larger lesions often require general anesthesia. Recent data suggest that early exposure to general anesthesia may have a negative effect on learning and behavior.…”
Section: Laser Therapy For Ihmentioning
confidence: 99%
“…Specifically, a total number of 90 infants were included with a median age of 3.0 months with a total number of 105 haemangiomas, and were treated doi:10.18282/jsd.v2.it1.109 using this particular laser device. The results showed that complete or near-complete clearance was achieved for 81% of the haemangiomas in terms of colour and 64% in terms of thickness [21] . Similar results were also found by a study conducted in Korea, in which a total number of 239 patients with skin types II-V participated and of whom, 37 patients had haemangiomas, and the same variable-pulse PDL method was used.…”
Section: Cutaneous Haemangiomasmentioning
confidence: 90%
“…Two studies, a level II prospective RCT 80 and a level V retrospective review, 81 have shown increased efficacy in the treatment of IHs with these lasers. Despite the availability of newer, more effective lasers, the literature still supports the use of these instruments mainly for the treatment of superficial rather than deep IHs.…”
Section: Pulsed Dye Laser Therapymentioning
confidence: 98%
“…75 The PDL has been used and studied for more than 30 years as an option for treatment of IHs, and, as a result, there is substantial level III-V evidence in the form of various case reports, retrospective reviews, and small, nonrandomized prospective studies supporting its efficacy in the literature. [76][77][78][79][80][81][82][83] In 2002, the first level III evidence comparing PDL therapy to observation in the treatment of IHs was performed by Batta and colleagues 84 and raised significant doubt surrounding its efficacy. The investigators' analysis revealed no benefit in the number of children whose lesions showed complete clearance or minimal residual signs at 1 year in the PDL versus observation group.…”
Section: Pulsed Dye Laser Therapymentioning
confidence: 98%